Realización de un diagnóstico organizacional en gestión de proyectos para la creación de una PMO en Mitsubishi Electric de Colombia ltda. (2015)
The Project Management environment has been taking a lot of strength in the culture of organizations of various industries in recent years. Within the strategic framework of organizations, challenges arise that companies must meet and that, in many cases should be undertaken projects that we want to get favorable results that would meet the strategic objectives. Given the above, it is relevant to ask How structured projects become? And how successful are they? In different contexts. Particularly in Colombia, it is important to note that the rise of the inclusion of project management standards by applying international recognition is growing in organizations; however, there are not enough studies to support the determination is made in the most appropriate way. It is definite to have an adequate level of maturity in organizations and thereby ensure that projects produce satisfactory results, as well as have qualified personnel with proficiency and skills to manage them. In this context, we decided to make a diagnosis, to determine the degree of maturity in project management organization in Colombia Mitsubishi Electric has, in order to create a PMO (Project Management Office).